External marketing relationship practice of quantity surveying firms in the selected states in Nigeria / Esther Ilori Ebunoluwa and Grace Kehinde Ojo - Ebunoluwa, Esther Ilori; Ojo, Grace Kehinde (UiTM Press, 2021)
It has been established that marketing is very significant to the success of any organization, especially in a competitive environment. In the Quantity surveying profession, marketing might be more relevant than other professions because it is less known. The significance of marketing and competitive business environment calls for effective marketing practice by Quantity Surveying Firms (QSFs). One of the effective ways is to build a strong external marketing relationship, which exists between a firm and its client. Therefore, this paper investigated the external marketing relationship practice of QSFs with a view to enhancing firms' productivity and client satisfaction. Forty-six (46) registered QSFs and fifty-nine (59) corporate clients in Lagos, Oyo, and Ondo States were assessed through questionnaire survey. Data were collected on the attributes of parties involved in external marketing. The collected data were analysed using Mean Item Scores (MIS) and Analysis of Variance (ANOVA). The results reveal important attributes of clients to include "pay on time (MS=4.59)", "willingness and readiness to take advice from the firm (MS=4.59)", and "make expectations known clearly to the firm (MS=4.54)". From the findings, clients averagely displayed these attributes. The result of ANOVA shows that firms viewed the importance of these clients' attributes in the same way at p>0.05 except for one of these attributes (making expectations known clearly to the firm), which firms viewed its importance differently at p<0.05. Furthermore, results show the important attributes of firms to include: "ability to give clients value for their money (MS=4.51)", "knowing clients' requirements (MS=4.51)", and "being attentive (MS=4.47)'. Findings show that these attributes were adequately displayed by QSFs. The perceptions of clients on the importance of these firms' attributes were the same at p>0.05. The study concluded by establishing attributes for strong external marketing relationship to include: "readiness of a client to take advice from the firm", "ability of a client to pay on time", "ability of a firm to satisfy the client", and "knowing the client's requirements". The study recommended that QSFs and clients should endeavour to possess and display these attributes for the enhancement of service delivery in terms of firms' productivity and clients' satisfaction.